A high-toughness polycarbonate composite material and preparation method thereof

By formulating modified PC resin and ABS resin, flexible silicone chains and hindered phenol structures are introduced, the brittleness and aging problems of polycarbonate materials are solved, and a high toughness and aging resistance polycarbonate composite materials are achieved.

CN118813025BActive Publication Date: 2025-04-08CHENGDU ZHENCAI PLASTIC MATERIAL CO LTD

Patent Information

Application Number
CN202411069914.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2025-04-08
Estimated Expiration
2044-08-06

AI Technical Summary

Technical Problem

Due to the rigidity and brittleness of the molecular chain, polycarbonate materials are prone to stress cracking under stress, and are sensitive to ultraviolet rays, which intensifies aging, limiting their application.

Method used

The composite material is formulated with modified PC resin and ABS resin. The modified PC resin introduces flexible silicone chains and hindered phenol structures through amine transesterification and grafting reactions, reducing the rigidity and internal stress of the polymer chain, and enhancing the toughness and aging resistance of the material.

Benefits of technology

It improves the strength and strength comprehensive performance and tolerance of polycarbonate composite materials, reduces the internal stress and aging speed of the material, and maintains the transparency and aesthetics of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004980556530000081
    Figure BDA0004980556530000081
  • Figure BDA0004980556530000091
    Figure BDA0004980556530000091
Patent Text Reader

Abstract

The invention relates to a high-toughness polycarbonate composite material and a preparation method thereof, and belongs to the technical field of polymer materials. The composite material comprises, by weight, 100 parts of modified PC resin, 10-15 parts of ABS resin, 4.5-6.5 parts of oleophilic silica and 0.8-1.1 parts of a processing aid. The modified PC resin is prepared by amine ester exchange of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) methyl propionate and diethanolamine to prepare an intermediate, and then the tertiary amine structure in the intermediate molecule is used to in-situ promote the ring opening of the grafted hydroxyl group and the terminal epoxy silicone oil, and introduce an organic silicon chain, and then the active amino group of p-aminophenol and the residual epoxy are opened, and the phenol structure is introduced for end-capping to prepare a modifier, and finally, the modifier is ester exchanged with bisphenol A and diphenyl carbonate to prepare the modified PC resin, and the composite material with the modified PC resin as a matrix has higher comprehensive strength and toughness performance than the existing PC / ABS material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high-toughness polycarbonate composite material and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) is a common high molecular polymer with carbonate groups in its molecular chain. It can be divided into aliphatic, aromatic and other categories. Currently, the industrial-scale production and application generally refers to bisphenol A polycarbonate, which has a high heat deformation temperature, glass transition temperature and heat resistance. It is also the only transparent material among the five major engineering plastics and is widely used in transportation, optical instruments, medical devices, packaging and other fields.

[0003] While polycarbonate has the above excellent comprehensive properties, it inevitably has some defects, such as the high rigidity and brittleness of the molecular chain, which makes it difficult for the material to undergo plastic deformation when subjected to stress, and thus easily produces stress cracking in the product. In addition, its molecular chain contains a large amount of carbonate structure, which is sensitive to ultraviolet rays and prone to aging, aggravating the stress cracking defect and seriously limiting the application of polycarbonate. In the prior art, polycarbonate and acrylonitrile-butadiene-styrene copolymer (ABS) are blended, and ABS is used as a toughening material, which can reduce the internal stress of polycarbonate to a certain extent, and a certain amount of anti-aging additives are compounded to slow down the aging of polycarbonate to a certain extent. However, these external admixtures have limited compatibility with polycarbonate, have a great influence on the mechanical properties of polycarbonate, and will cause the haze of polycarbonate to increase, affecting its transparent aesthetics. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a high-toughness polycarbonate composite material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A high-toughness polycarbonate composite material, comprising, by weight:

[0007] 100 parts of modified PC resin, 10-15 parts of ABS resin, 4.5-6.5 parts of oleophilic silica and 0.8-1.1 parts of processing aid.

[0008] The modified PC resin is prepared by the following method:

[0009] Step A1: methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diethanolamine and anhydrous tetrahydrofuran are mixed, nitrogen is introduced, the temperature is raised to 45-55° C., stirring is applied at 60-90 rpm, sodium hydride is added intermittently to react for 3-4 hours, and tetrahydrofuran is removed by rotary evaporation after the reaction is completed. The substrate is washed with water and dried in vacuo to obtain an intermediate;

[0010] Furthermore, the dosage ratio of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diethanolamine, sodium hydride and anhydrous tetrahydrofuran is 0.1 mol: 0.105-0.11 mol: 0.12-0.15 g: 80-110 mL, and sodium hydride is an alkaline catalyst to promote amine ester exchange between methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and diethanolamine.

[0011] Step A2: The intermediate, epoxy-terminated silicone oil and ethyl acetate are mixed, heated to 60-70°C, stirred at 180-240 rpm, reacted for 2-3 hours, then cooled to 40-50°C, and an acetone solution of p-aminophenol is added, and the reaction is continued for 1-1.5 hours. After the reaction is completed, the ethyl acetate is removed by rotary evaporation, and the substrate is washed with ethanol and dried to obtain a modifier;

[0012] Furthermore, the epoxy content of the intermediate, the epoxy-terminated silicone oil, the dosage ratio of p-aminophenol and ethyl acetate is 0.1 mol: 0.11-0.12 mol: 20-30 mmol: 180-250 mL, and the tertiary amine structure in the intermediate molecule promotes the ring-opening of its grafted hydroxyl group and the epoxy-terminated silicone oil in situ, and then the active amino group of p-aminophenol and the residual epoxy are opened to introduce the phenol structure for end-capping.

[0013] Furthermore, the room temperature viscosity of the epoxy-terminated silicone oil is not higher than 50 mm 2 / s.

[0014] Step A3: Mix bisphenol A and diphenyl carbonate as a base material, introduce nitrogen protection, preheat to 160-170° C., add a modifier and a catalyst, mix and react for 1.2-1.6 hours, then reduce the pressure and maintain the pressure of the reaction system below 1 kPa, then heat to 280-300° C., continue to react for 2.5-3.2 hours, and discharging and pelletizing after the reaction is completed to obtain a modified PC resin;

[0015] Furthermore, the molar ratio of bisphenol A to diphenyl carbonate in the base material is 1:1.19-1.24, the amount of the modifier is 10-15wt% of the base material, and the catalyst is preferably a mixture of dibutyltin dilaurate and sodium tetraphenylborate, and the amount of the catalyst is 50-80ppm.

[0016] Preferably, the oleophilic silica is selected from nano-scale powder, which has less influence on the transparency of the composite material.

[0017] Preferably, the processing aid is selected from stearate, which has good lubricity to the composite material and is beneficial to the molding process of the composite material.

[0018] A preparation method of a high-toughness polycarbonate composite material, specifically comprising the following steps: uniformly mixing the raw materials in a high-speed mixer, loading the raw materials into a mixing kettle, mixing the raw materials at 180±5°C for 30 minutes under nitrogen protection, discharging the raw materials and slicing the raw materials to obtain the high-toughness polycarbonate composite material.

[0019] Beneficial effects of the present invention:

[0020] The invention adopts independently developed modified PC resin and ABS resin to prepare composite materials, which has higher comprehensive toughness and tolerance than existing PC / ABS composite materials; the modified PC resin is prepared by amine ester exchange of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) methyl propionate and diethanolamine to prepare an intermediate, and then the tertiary amine structure in the intermediate molecule is used to promote the ring opening of the grafted hydroxyl group and the terminal epoxy silicone oil in situ, and the organic silicon chain is introduced, and then the active amino group of p-aminophenol and the residual epoxy are opened, and the phenol structure is introduced to block the end to prepare a modifier, and finally, the modifier and bisphenol A are ester exchanged with diphenyl carbonate to prepare the modified PC resin; the modified monomer is introduced into the polymerization chain The introduction of flexible silicone chains into the block reduces the rigidity of the polymer chain and improves the lubricity between the molecular chains. During the molding process, the flexible silicone chains are deformed to reduce the internal stress in the polymer, making it less likely to cause micro cracks when subjected to external forces or solvent corrosion, resulting in a decrease in the toughness of the material. In addition, after copolymerization of the modified monomer blocks, hindered phenol structures are uniformly introduced between the macromolecular chains, which can effectively capture the free radicals generated by the light and heat environment and effectively slow down the generation of micro cracks in the internal stress concentration area caused by aging. Thanks to the improved toughness of the modified PC resin matrix and the reduction in the proportion of doping systems such as ABS resin, the good transparency of the polycarbonate material can be maintained, and it has a higher aesthetics when used especially in decorative materials. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1: This example prepares a high-toughness polycarbonate composite material. The specific implementation process is as follows:

[0023] (1) Preparation of modified PC resin

[0024] Step A1: Mix methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diethanolamine and anhydrous tetrahydrofuran, introduce nitrogen protection, heat to 55°C, stir at 90rpm, take equal amounts of sodium hydride and divide them into three portions, add them intermittently for 30 minutes, continue the constant temperature reaction after the addition is complete, and control the total addition reaction time of sodium hydride to be 3 hours, wherein the amount ratio of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diethanolamine, sodium hydride and anhydrous tetrahydrofuran is 0.1 mol: 0.11 mol: 0.15 g: 110 mL. After the reaction is completed, remove tetrahydrofuran by rotary evaporation, wash the substrate with water, and vacuum dry to obtain an intermediate.

[0025] Step A2: Mix the intermediate, epoxy-terminated silicone oil and ethyl acetate, heat to 70°C, stir at 240 rpm, react for 2 hours, then cool to 50°C, add acetone solution of p-aminophenol, and continue to react for 1 hour, wherein the acetone solution of p-aminophenol is a saturated acetone solution of p-aminophenol at room temperature, and the epoxy-terminated silicone oil is a raw material of X-22-163A, with a room temperature viscosity of 30 mm 2 / s, the epoxy content of the intermediate, the epoxy-terminated silicone oil, the amount ratio of p-aminophenol and ethyl acetate is 0.1 mol: 0.12 mol: 30 mmol: 250 mL, and the ethyl acetate is removed by rotary evaporation after the reaction is completed. The substrate is washed with ethanol and dried to obtain a modifier.

[0026] Step A3: Take bisphenol A and diphenyl carbonate as a base material, pass nitrogen protection, preheat to 170°C, add modifier and catalyst, mix and react for 1.2 hours, then reduce the pressure and maintain the pressure of the reaction system below 1 kPa, and then heat to 300°C and continue to react for 2.5 hours, wherein the molar ratio of bisphenol A to diphenyl carbonate is 1:1.19, the amount of the modifier is 10wt% of the base material, and the catalyst is premixed with dibutyltin dilaurate and sodium tetraphenylborate in a mass ratio of 2:1, and the amount is 80ppm. After the reaction is completed, the material is discharged and pelletized to obtain a modified PC resin.

[0027] (2) Preparation of composite materials

[0028] Ingredients: 100 parts of modified PC resin, prepared in this embodiment, 15 parts of ABS resin, Toyolac 990X88 raw material was used in the implementation process; 6.5 parts of lipophilic silica, VK-SP30S raw material was used in the implementation process, with an average particle size of 30 nm; 1.1 parts of processing aid, polyethylene glycol distearate was used in the implementation process.

[0029] Mixing: Add the above raw materials into a high-speed mixer, stir and mix at 800 rpm for 10 minutes, put into a mixing kettle, mix at 180±5°C for 30 minutes under nitrogen protection, and cut the material into slices to obtain a high-toughness polycarbonate composite material.

[0030] Example 2: This example prepares a high-toughness polycarbonate composite material. The specific implementation process is as follows:

[0031] (1) Preparation of modified PC resin

[0032] Step A1: Mix methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diethanolamine and anhydrous tetrahydrofuran, introduce nitrogen protection, heat to 45°C, stir at 60rpm, take equal amounts of sodium hydride and divide them into three portions, add them intermittently for 40 minutes, continue the constant temperature reaction after the addition is complete, and control the total addition reaction time of sodium hydride to be 4 hours, wherein the amount ratio of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diethanolamine, sodium hydride and anhydrous tetrahydrofuran is 0.1 mol: 0.105 mol: 0.12 g: 80 mL. After the reaction is completed, remove tetrahydrofuran by rotary evaporation, wash the substrate with water, and vacuum dry to obtain an intermediate.

[0033] Step A2: Mix the intermediate, epoxy-terminated silicone oil and ethyl acetate, heat to 60°C, stir at 180 rpm, react for 3 hours, then cool to 40°C, add acetone solution of p-aminophenol, and continue to react for 1.5 hours, wherein the acetone solution of p-aminophenol is a saturated acetone solution of p-aminophenol at room temperature, and the epoxy-terminated silicone oil is a KF-105 raw material with a room temperature viscosity of 15 mm 2 / s, the epoxy content of the intermediate, the epoxy-terminated silicone oil, the amount ratio of p-aminophenol and ethyl acetate is 0.1 mol: 0.11 mol: 20 mmol: 180 mL, and the ethyl acetate is removed by rotary evaporation after the reaction is completed. The substrate is washed with ethanol and dried to obtain a modifier.

[0034] Step A3: Take bisphenol A and diphenyl carbonate as a base material, pass nitrogen protection, preheat to 160°C, add modifier and catalyst, mix and react for 1.6 hours, then reduce the pressure and maintain the pressure of the reaction system below 1 kPa, and then heat to 280°C and continue to react for 3.2 hours, wherein the molar ratio of bisphenol A to diphenyl carbonate is 1:1.24, the amount of the modifier is 10wt% of the base material, and the catalyst is premixed with dibutyltin dilaurate and sodium tetraphenylborate in a mass ratio of 2:1, and the amount is 50ppm. After the reaction is completed, the material is discharged and pelletized to obtain a modified PC resin.

[0035] (2) Preparation of composite materials

[0036] Ingredients: 100 parts of modified PC resin, prepared in this embodiment, 10 parts of ABS resin, Toyolac 990X88 raw material was used in the implementation process; 4.5 parts of lipophilic silica, VK-SP30S raw material was used in the implementation process, with an average particle size of 30 nm; 0.8 parts of processing aid, polyethylene glycol distearate was used in the implementation process.

[0037] Mixing: Add the above raw materials into a high-speed mixer, stir and mix at 800 rpm for 10 minutes, put into a mixing kettle, mix at 180±5°C for 30 minutes under nitrogen protection, and cut the material into slices to obtain a high-toughness polycarbonate composite material.

[0038] Example 3: This example prepares a high-toughness polycarbonate composite material. The specific implementation process is as follows:

[0039] (1) Preparation of modified PC resin

[0040] Step A1: methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diethanolamine and anhydrous tetrahydrofuran are mixed, nitrogen is introduced for protection, the temperature is raised to 50°C, stirring is applied at 90 rpm, equal amounts of sodium hydride are divided into three portions, and added intermittently for 40 minutes. After the addition is complete, the reaction is continued at a constant temperature, and the total addition reaction time of sodium hydride is controlled to be 4 hours, wherein the amount ratio of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diethanolamine, sodium hydride and anhydrous tetrahydrofuran is 0.1 mol: 0.108 mol: 0.15 g: 100 mL. After the reaction is completed, tetrahydrofuran is removed by rotary evaporation, the substrate is washed with water, and vacuum dried to obtain an intermediate.

[0041] Step A2: Mix the intermediate, epoxy-terminated silicone oil and ethyl acetate, heat to 65°C, stir at 240 rpm, react for 2.2 hours, then cool to 45°C, add acetone solution of p-aminophenol, and continue to react for 1.2 hours, wherein the acetone solution of p-aminophenol is a saturated acetone solution of p-aminophenol at room temperature, and the epoxy-terminated silicone oil is a KF-105 raw material with a room temperature viscosity of 15 mm 2 / s, the epoxy content of the intermediate, the epoxy-terminated silicone oil, the amount ratio of p-aminophenol and ethyl acetate is 0.1 mol: 0.115 mol: 25 mmol: 220 mL, and the ethyl acetate is removed by rotary evaporation after the reaction is completed. The substrate is washed with ethanol and dried to obtain a modifier.

[0042] Step A3: Take bisphenol A and diphenyl carbonate as a base material, pass nitrogen protection, preheat to 170°C, add modifier and catalyst, mix and react for 1.5 hours, then reduce the pressure and maintain the pressure of the reaction system below 1 kPa, and then heat to 290°C and continue to react for 3 hours, wherein the molar ratio of bisphenol A to diphenyl carbonate is 1:1.22, the amount of the modifier is 12wt% of the base material, and the catalyst is premixed with dibutyltin dilaurate and sodium tetraphenylborate in a mass ratio of 2:1, and the amount is 70ppm. After the reaction is completed, the material is discharged and pelletized to obtain a modified PC resin.

[0043] (2) Preparation of composite materials

[0044] Ingredients: 100 parts of modified PC resin, prepared in this embodiment, 10-15 parts of ABS resin, Toyolac 990X88 raw material was used in the implementation process; 4.5-6.5 parts of lipophilic silica, VK-SP30S raw material was used in the implementation process, with an average particle size of 30 nm; 0.8-1.1 parts of processing aid, polyethylene glycol distearate was used in the implementation process.

[0045] Mixing: Add the above raw materials into a high-speed mixer, stir and mix at 800 rpm for 10 minutes, put into a mixing kettle, mix at 180±5°C for 30 minutes under nitrogen protection, and cut the material into slices to obtain a high-toughness polycarbonate composite material.

[0046] Comparative Example 1

[0047] This comparative example refers to Example 3, except that the modified PC resin is replaced with CALIBRE 302-15 raw material (containing an anti-ultraviolet stabilizer), and the rest of the implementation process is exactly the same.

[0048] Comparative Example 2

[0049] This comparative example refers to comparative example 1, except that the amount of ABS resin is adjusted to 25 parts, and the rest of the implementation process is exactly the same.

[0050] The composite material prepared above was hot pressed into a sheet at a temperature of 300°C and a pressure of 1.5MPa using a flat vulcanizer; samples were taken from the sheet and tensile tested according to GB / T 1040.1-2018 standard, and the strength and toughness of the material were measured by the tensile index of the sample; the haze of the sample was tested according to GB / T 2410-2008 standard; the specific test data are shown in Table 1:

[0051] Table 1

[0052] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Tensile strength / MPa 65.9 68.4 67.2 62.5 55.3 Elongation at break / % 66.12 63.70 68.09 53.82 60.04 Haze / % 6.4 5.7 5.9 6.9 8.5

[0053] It can be seen from the test data in Table 1 that the blending of ABS and polycarbonate can improve the toughness to a certain extent, but it will cause a sharp deterioration in strength and an increase in haze. The polycarbonate composite material prepared in the embodiment has more excellent comprehensive strength and toughness properties than the comparative example, while maintaining a reduced haze level.

[0054] The sample was immersed in carbon tetrachloride at a temperature of 25°C for 24 hours. After cleaning, a tensile test was performed, and the change rate was calculated by comparing with the initial tensile data. The sample was placed in an aging box, and the power of the ultraviolet light source was controlled to be 200W, the temperature was 60°C, and the aging time was 72 hours. After that, a tensile test was performed, and the change rate was calculated by comparing with the initial tensile data. The specific test data are shown in Table 2:

[0055] Table 2

[0056]

[0057]

[0058] Note: “-” indicates reduced performance.

[0059] It can be seen from the test data in Table 2 that the blending of ABS and polycarbonate has a positive effect on the solvent resistance and aging resistance of polycarbonate, but the mechanical properties of the embodiment are less decreased than those of the comparative example, and the embodiment has better tolerance.

[0060] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0061] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high-toughness polycarbonate composite material, characterized in that: The raw materials include the following in parts by weight: 100 parts of modified PC resin, 10-15 parts of ABS resin, 4.5-6.5 parts of oleophilic silica and 0.8-1.1 parts of processing aid; The modified PC resin is prepared by the following method: Step A1: methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diethanolamine and anhydrous tetrahydrofuran are mixed, nitrogen is introduced for protection, the temperature is raised to 45-55° C., and sodium hydride is added intermittently with stirring for 3-4 hours. After the reaction is completed, tetrahydrofuran is removed by rotary evaporation, the substrate is washed with water, and vacuum dried to obtain an intermediate; Step A2: The intermediate, epoxy-terminated silicone oil and ethyl acetate are mixed, heated to 60-70°C, stirred and reacted for 2-3h, then cooled to 40-50°C, and an acetone solution of p-aminophenol is added, and the reaction is continued for 1-1.5h. After the reaction is completed, the ethyl acetate is removed by rotary evaporation, and the substrate is washed with ethanol and dried to obtain a modifier; Step A3: Mix bisphenol A and diphenyl carbonate as a base material, introduce nitrogen protection, preheat to 160-170°C, add modifier and catalyst, mix and react for 1.2-1.6h, then reduce the pressure and maintain the pressure of the reaction system below 1kPa, then heat to 280-300°C, continue to react for 2.5-3.2h, and after the reaction is completed, discharge and pelletize to obtain modified PC resin.

2. A high-toughness polycarbonate composite material according to claim 1, characterized in that: The usage ratio of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diethanolamine, sodium hydride and anhydrous tetrahydrofuran is 0.1 mol: 0.105-0.11 mol: 0.12-0.15 g: 80-110 mL.

3. A high-toughness polycarbonate composite material according to claim 2, characterized in that: The usage ratio of the intermediate, the epoxy content of the epoxy-terminated silicone oil, p-aminophenol and ethyl acetate is 0.1 mol: 0.11-0.12 mol: 20-30 mmol: 180-250 mL.

4. The high-toughness polycarbonate composite material according to claim 3, characterized in that: The room temperature viscosity of epoxy silicone oil is not higher than 50mm 2 / s.

5. The high-toughness polycarbonate composite material according to claim 4, characterized in that: The molar ratio of bisphenol A to diphenyl carbonate in the base material is 1:1.19-1.24, the dosage of the modifier is 10-15wt% of the base material, the catalyst is a mixture of dibutyltin dilaurate and sodium tetraphenylborate, and the dosage of the catalyst is 50-80ppm.

6. The high-toughness polycarbonate composite material according to claim 1, characterized in that: The lipophilic silica is nano-scale powder.

7. The high-toughness polycarbonate composite material according to claim 1, characterized in that: The processing aid is stearate.

8. The method for preparing a high-toughness polycarbonate composite material according to any one of claims 1 to 7, characterized in that: The specific operation is as follows: the raw materials are mixed evenly and loaded into a mixing kettle, and mixed at 180±5°C for 30 minutes under nitrogen protection, and the material is cut into slices to obtain a high-toughness polycarbonate composite material.

Citation Information

Patent Citations

  • Carboxamide and amine compounds as well as preparation method and applications thereof

    CN105693545A

  • Carboxamide compounds, a preparing method thereof and applications of the compounds

    CN108164446A

Cited By

  • A high toughness polycarbonate composite

    CN122541978A